Sustainable renovation : strategies for commercial building systems and envelope - Gelfand, Lisa (Wiley series in sustainable design., 2012)
The complete resource on performing sustainable renovations for both Historic and modern existing buildingsThis forward-looking and insightful guide explores how the sustainable renovation of existing buildings presents great opportunities for initiating extensive changes in the performance of the built environment. Great examples of existing building upgrades are examined, illustrating how to do sustainable renovations, along with current design approaches for radically improving the functionality of existing prewar, postwar, and late modern buildings. Sustainable Renovation saves its key foc.